Shakespeare as Literary Dramatist - Erne, Lukas (New York, 2013)
"In this groundbreaking study, Lukas Erne argues that Shakespeare, apart from being a playwright who wrote theatrical texts for the stage, was also a literary dramatist who produced reading texts for the page. The usual distinction that has been set up between Ben Jonson carefully preparing his manuscripts for publication, and Shakespeare the man of the theatre, writing for his actors and audience, indifferent to his plays as literature, is questioned in this book. Examining the evidence from early published playbooks, Erne argues that Shakespeare wrote many of his plays with a readership in mind and that these "literary" texts would have been abridged for the stage because they were too long for performance. The variant early texts of Romeo and Juliet, Henry V, and Hamlet are shown to reveal important insights into the different media for which Shakespeare designed his plays."--Jacket